The role of ultrasonography in differential diagnosis of degenerative disk disease of the lumbar spine - Ponomarenko, Svetlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To improve the diagnostics of lumbar degenerative disc disease through the development and implementation of complex of ultrasound criteria into the clinical practice. Methods: There were examined 128 patients aged from 20 to 60 years with degenerative diseases of the lumbar spine, as well as 21 healthy subjects between the ages from 20 and 40 as a comparative group. Results: We in¬vestigated diagnostic capabilities of ultrasonography in patients with degenerative processes in the intervertebral discs (IVD) of different severity. There were defined ultrasound criteria for protru¬sions, IVD herniations, epiduritis, scar-adhesions in the epidural space, and the yellow ligament hypertrophy. The main feature that distinguishes the protrusion from other pathological conditions on the border of IVD and the spinal canal is an absence of the fibrous ring ruptures in the area of protrusions. When rendering ruptures of the disk we diagnosed IVD herniation. To determine the type of herniation using ultrasonography there has been proposed and patented a method of ultrasound diagnostics of the lumbar spine IVD herniation which clearly defined the localization of posterior herniation. There were evaluated and compared the efficiency and informativeness of ultrasonography in different types of IVD protrusions and herniations. Conclusions: An initial stage of the degenerative process in IVD is characterized by increased echo-genicity, heterogeneity in echostructure of the nucleus pulposus, expansion of the boundaries between it and the fibrous ring. Ex¬pressed stages of degenerative disk disease characterize with com¬promising of the integrity of the fibrous ring and the formation of IVD herniations, development of reactive epiduritis and adhesions in epidural space. It was demonstrated a high information content of the ultrasonic method for visualization of localization, direction and size of herniations: sensitivity — 89.2 %; specificity — 66.6 %; accuracy — 87.1 %.